Brain function changes reveal rapid antidepressant effects of nitrous oxide for treatment-resistant depression:Evidence from task-state EEG. (April 2023) - Shao, Xuexiao; Yan, Danfeng; Kong, Wenwen; Sun, Shuting; Liao, Mei; Ou, Wenwen; Zhang, Yan; Zheng, Fang; Li, Xiaowei; Li, Lingjiang; Hu, Bin
Highlights: This study provides the EEG evidence that nitrous oxide-induced brain function changes for treatment-resistant depression (TRD). This study firstly evaluated the efficacy of nitrous oxide for TRD based on event-related potential (ERP) components and functional connectivity networks (FCNs) methods. These findings may suggest that nitrous oxide improves depression symptoms for TRD by altering brain function. The network metrics in FCNs may provide new biological explanations for studying the rapid antidepressant effects of nitrous oxide on brain function. Abstract: Nitrous oxide has rapid antidepressant effects in patients with treatment-resistant depression (TRD), but its underlying mechanisms of therapeutic actions are not well understood. Moreover, most of the current studies lack objective biological indicators to evaluate the changes of nitrous oxide-induced brain function for TRD. Therefore, this study assessed the effect of nitrous oxide on brain function for TRD based on event-related potential (ERP) components and functional connectivity networks (FCNs) methods. In this randomized, longitudinal, placebo-controlled trial, all TRD participants were divided into two groups to receive either a 1-hour inhalation of nitrous oxide or a placebo treatment, and they took part in the same task-state electroencephalogram (EEG) experiment before and after treatment. The experimental results showed that nitrous oxide improved depressive symptoms better than placebo in terms of 17-Hamilton Depression Rating Scale score (HAMD-17). Statistical analysis based on ERP components showed that nitrous oxide-induced significant differences in amplitude and latency of N1, P1, N2, P2. In addition, increased brain functional connectivity was found after nitrous oxide treatment. And the change of network metrics has a significant correlation with decreased depressive symptoms. These findings may suggest that nitrous oxide improves depression symptoms for TRD by modifying brain function.